Comparative Study of Blood Hemoglobin between Calculated Method through ABG Analyzer and Impedance Method through Fully Automated Blood Cell Counter - Arvi V Mehta; Sapna P Patel; Hina B Baraiya; Piyush B Tailor (Indian Journal of Medical Biochemistry)
Background: In routine clinical laboratory practice, hemoglobin estimation is done through an automated blood cell counter, which is a fast, inexpensive and convenient method of estimation. In contrast to these conventional laboratory procedures, hemoglobin is one of the calculated parameters in the arterial blood gas (ABG) analyzer in emergency and intensive care units. As per ISO 15189 and National Accreditation Board for Testing and Calibration Laboratories (NABL-112) guideline, it is necessary to compare and justify the result of the parameters when it is done through multiple instruments or multiple methods. Materials and methods: A total of 100 samples of ABG analysis were collected and hemoglobin estimation was done from Siemens RAPID point 500e ABG analyzer by co-oximetry method and HORIBA fully automated blood cell counter by electric impedance method. Data was collected and analyzed by Bland-Altman plot and linear regression graph using Microsoft Excel. Results: After analyzing the data, we concluded that Siemens RAPID point 500e ABG analyzer gives 14.77% higher result of hemoglobin in compared to HORIBA fully automated blood cell counter. Conclusion: The laboratory has derived its own corrective factor to make the result of hemoglobin comparable for both instruments and methods by using slope and intercept derived from linear regression graph.